The Dynamics of Restraint in Côte d'Ivoire. (8th January 2013) - Allouche, Jeremy; Zadi Zadi, Patrick Anderson
Abstract Research on conflict prevention has mainly focused on the causes of war and post‐conflict reconstruction. Our knowledge on how civilians manage to contain violence in unstable and conflict environments is, however, very limited. This article aims to understand, in the context of the civil war in Côte d'Ivoire, how and why 'islands of peace' emerge during outbreaks of violence. It identifies both the local and structural conditions and mechanisms (including formal and informal) that help to mitigate violence and encourage restraint in conflict‐affected and unstable situations. Our research and analysis has focused on the western region, which is the epicentre of violence. Semi‐structured interviews with Young Patriots members, the military, the business community, representatives of women's NGOs, traditional leaders and representatives of the religious community, along with interviews in Abidjan, provided the primary data for our analysis.